Sonic Agency Sound and Emergent Forms of Resistance - LaBelle, Brandon (Sonics, 2018)
In a world dominated by the visual, could contemporary resistances be auditory? Sonic Agency highlights sound's invisible, disruptive and affective qualities, and asks whether the unseen nature of sound can support a political transformation.